Faktor – Faktor yang Mempengaruhi Nilai Perusahaan - Indira Putriningtyas; Fitri Yetty; Dahlia Pinem (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2019)
This research was conducted to test the influence of the leverage, liquidity and sales growth of firm value. “Doing research on the company’s Sub Sector Miscellaneous Industry which listed on the Indonesia Stock Exchange as a sample. The technique of determination of the sample using the method of purposive sampling (purposive sampling method). The selection of the sample of 43 company Sub Sector Miscellaneous Industry were listed on the Indonesia Stock Exchange in 2014-2017 produce company 20 is acceptable. “Data analysis is done using the Microsoft Excel 2016 and hypothesis testing in this study using a Panel Data Regression Analysis with the program E-Views 9.0 and the level of significance of 5%. The results of the test were obtained (1) the leverage is represented by DER effect positive significantly to firm value, (2) liquidity is represented by CR no effect significantly to the firm value, (3) Sales Growth is represented by SG no effect significantly to firm value”.